2016
DOI: 10.1007/s13577-016-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model reveals that Mfsd2a is critical for unfolded protein response upon exposure to tunicamycin

Abstract: Major facilitator superfamily domain containing 2a (Mfsd2a) is a member of the major facilitator superfamily. Mfsd2a functions as a transporter for docosahexaenoic acid and also plays a role in the unfolded protein response (UPR) upon tunicamycin (TM) exposure. UPR is involved in the pathogenesis of various human diseases. TM and thapsigargin are representative experimental reagents that induce UPR. To elucidate the detailed function of Mfsd2a in UPR in vivo, we generated Mfsd2a-deficient mice and investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Consistent with a role in transport, Mfsd2a was shown to be localized to the plasma membrane (Reiling et al, ). The role of Mfsd2a as a tunicamycin transporter was further supported by in vivo studies as well (Moritake et al, ).…”
Section: Roles Of Mfsd2a In Physiological and Pathological Conditionsmentioning
confidence: 84%
“…Consistent with a role in transport, Mfsd2a was shown to be localized to the plasma membrane (Reiling et al, ). The role of Mfsd2a as a tunicamycin transporter was further supported by in vivo studies as well (Moritake et al, ).…”
Section: Roles Of Mfsd2a In Physiological and Pathological Conditionsmentioning
confidence: 84%
“…2D). Given the obvious escape from inhibition of N-glycosylation, we examined expression of the lysophosphatidyl choline / docosahexaenoate transporter Mfsd2a, which is known to encode the primary plasmalemmal transport mechanism for TUN (17,18). Indeed, PCCL3 cells that had been slowly adapted to increasing doses of TUN eventually suppressed Mfsd2a mRNA expression > 500-fold ( Fig.…”
Section: Development Of a Cell Culture Model Of Chronic Continuous Ermentioning
confidence: 99%
“…[ 20 ] The major pathological manifestations of TM toxicity occur foremost in the liver through gross pathological examination. [ 12 ] However, TM@TTP and DOX@TTP–HA exhibited limited influence on liver function (Figure 6C), suggesting low in vivo hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10b ] Mfsd2a is closely related to the unfolded protein response upon TM exposure. [ 12 ] It has been reported that mice treated with TM have >1000‐fold more virus in the brain after virus infection as compared to untreated mice. [ 13 ] TM did not alter the viremia profiles of these viruses nor the virus replication in the brain itself.…”
Section: Introductionmentioning
confidence: 99%